PENINGKATAN PANGSAPASAR PERUSAHAAN RITEL MELALUI CUSTOMER SATISFCATION - ANSWAN, YASSAR; SUTRISNO, NUNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study was to determine the effect of Emotional Support, Instrumental Support, Informational Support and Appraisal Support on Customer Satisfaction of Lotte Mart customers in DKI Jakarta. The population used in this research is Lotte Mart customers who live in DKI Jakarta. The sample used was 147 respondents obtained using purposive sampling technique. The measurement of each variable in this study uses a 5-point Likert scale. The test tool for processing research data is using SPSS 25 software. The results of this study indicate that there is an influence of Emotional Support, Instrumental Support, and Appraisal Support on Customer Satisfaction for Lotte Mart customers in DKI Jakarta. While there is no influence between Informational Support on Customer Satisfaction.